Urban greenspace under a changing climate: Benefit or harm for allergies and respiratory health? - Zhao, Tianyu; Heinrich, Joachim; Brauer, Michael; Fulman, Nir; Idrose, Nur Sabrina; Baumbach, Clemens; Buters, Jeroen T. M.; Markevych, Iana; Ritz, Beate; Tham, Rachel; Yang, Bo-Yi; Zeng, Xiao-Wen; et al. (Environmental epidemiology, 2025)
An increasing proportion of the world’s population lives in urban settings that have limited greenspace. Urbanization puts pressure on existing greenspace and reduces its access. Climate impacts, including increased temperature and extreme weather events, challenge the maintenance of urban vegetation, reducing its ecosystem services and benefits for human health. Although urban greenspace has been positively associated with numerous health indicators, the evidence for allergies and respiratory health is much less clear and mixed. To address these uncertainties, a workshop with 20 global participants was held in Munich, Germany, in May 2024, focusing on the impact of greenspace-related co-exposures on allergies and respiratory health. This narrative review captures key insights from the workshop, including the roles of urban greenspace in (1) climate change mitigation, (2) interactions with pollen, and (3) emissions of biogenic volatile organic compounds and their byproducts, such as ozone. Additionally, it presents research and stakeholder recommendations from the workshop. Future studies that integrate advanced greenspace exposure assessments and consider the interplay of greenspace with pollen and biogenic volatile organic compounds, along with their relevant byproducts are needed. Increased public awareness and policy actions will also be essential for developing urban greenspace that maximizes health benefits, minimizes risks, and ensures resilience amid a changing climate and rapid urbanization.
Gesehen am 12.06.2025